Analisis Kinerja Pegawai Dalam Memberikan Pelayanan Kepada Masyarakat Pada Kantor Desa Ciwidey Kab.Bandung - Putri, Silvianisa Saleha; Kusuma, Siska Fajar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the performance of employees in providing services to the community at the Ciwidey Village Office, Bandung Regency. The research method used is descriptive qualitative with data collection techniques through interviews with three employees and three community members. The results indicate that overall employee performance is good, characterized by discipline, responsiveness, and timeliness in service. However, several challenges exist, such as uneven workload distribution, the need for digital skills improvement, and adaptation to service innovations. The community responded positively to the quality of service, particularly in terms of friendliness and speed, although there is still room for improvement. The implications of this research emphasize the importance of technology training, workload redistribution, and strengthening participatory evaluation systems. Recommendations include providing support facilities, employee career development, and increasing community participation in providing feedback. By implementing these recommendations, it is hoped that the quality of service at the Ciwidey Village Office can be further enhanced to achieve more effective and accountable village governance.